Venture capital in Europe - Gregoriou, Greg N., 1956-; Kooli, Maher; Kräussl, Roman; ScienceDirect eBooks (Amsterdam ; Boston : Butterworth-Heinemann, 2007)
Until recently, only the United States had an active venture capital market. This is changing rapidly, as many other countries have experienced rapid growth in venture capital financing over the past five years. This book contains new scientific articles showcasing the latest research on venture capital in Europe. Venture capital investment remains a hot topic with portfolio managers, individual investors, academics worldwide. This book examines in detail all the major issues regarding venture capital investment: contracting, financing, regulation, valuation, etc. and identifies new trends in the venture capital arena. Features a foreword by Josh Lerner. *The only book in which academics from around the world present the latest research on venture capital in Europe *Covers all of Europe as well as including overview papers about venture capital industry, public and private venture capital, valuation, financing, contracting, structuring, regulation, etc. *Comprehensive, authoritative coverage.
Venture capital in Europe: closing the gap to the U.S. -- Public venture capital across Europe: a 15-year perspective -- Why are venture capital markets well developed in some countries but comparatively small in others: evidence from Europe -- A survey of the venture capital industry in Central and Eastern Europe -- Venture capital in European transition economies -- Recommendations for the development of a European Venture Capital regulatory corpus: lessons from the USA -- Productivity growth in Spanish venture-backed firms -- Is the Spanish public-sector effective in backing venture capital -- A review of the venture capital industry in Italy -- Exit strategy and the intensity of exit-directed activities among venture capital backed entrepreneurs in Sweden -- Private equity fund managers over-value their company investments -- A search model of Venture Capital, entrepreneurship, and unemployment -- Capital structure in new technology-based firms: venture capital-backed versus non-venture capital-backed firms in the Irish software sector -- German business ventures enterpreneurs, financing and success factors -- Financing practices in the German Venture Capital industry: an empirical study -- Covenants in Venture Capital contracts: theory and empirical evidence from the German capital market -- Supply and demand of venture capital for biotech firms: the case of the Belgian regions of Wallonia and Brussels -- Efficiency of VC firms using data envelopment analysis -- Agency theory and management buy-out: the role of venture capitalists -- Does the value of Venture Capital vary over the investee life cycle? -- evidence from Irish investees -- German banks as venture capitalists -- Long-run venture-backed IPO performance analysis of italian family-owned firms: what role do closed-end funds play? -- Securitisation and venture capital fund-raising -- Total loss risk in European vs. U.S. based venture capital investments.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Venture capital -- Europe; BUSINESS & ECONOMICS -- Finance; Venture capital; Europe; Risicokapitaal; Europa (geografie); Electronic books